2021
DOI: 10.1016/j.wss.2021.100037
|View full text |Cite
|
Sign up to set email alerts
|

Understanding changes in park visitation during the COVID-19 pandemic: A spatial application of big data

Abstract: In the spring of 2020, the COVID-19 pandemic changed the daily lives of people around the world. In an effort to quantify these changes, Google released an open-source dataset pertaining to regional mobility trends—including park visitation trends. Changes in park visitation are calculated from an earlier baseline period for measurement. Park visitation is robustly linked to positive wellbeing indicators across the lifespan, and has been shown to support wellbeing during the COVID-19 pandemic. Therefore, this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(59 citation statements)
references
References 69 publications
(99 reference statements)
1
47
0
1
Order By: Relevance
“…One option would be to further explore the role of multi-level values on green space visitation (building on van Riper et al, 2019). Another option would be to integrate individual, organizational, and interpersonal/relational factors in models of green space visitation in addition to environmental factors such as proximity of leisure facilities, road connectivity, population density, seasonal changes, altitude and traffic speed (see (Liu H. et al, 2017) for overview; Rice and Pan, 2021). Also, it would be worthwhile repeating this same study by exploring a range of different leisure activities, recognizing that park visitation is influenced by leisure motivation (Kabisch et al, 2021).…”
Section: Implications For Ugi Managementmentioning
confidence: 99%
“…One option would be to further explore the role of multi-level values on green space visitation (building on van Riper et al, 2019). Another option would be to integrate individual, organizational, and interpersonal/relational factors in models of green space visitation in addition to environmental factors such as proximity of leisure facilities, road connectivity, population density, seasonal changes, altitude and traffic speed (see (Liu H. et al, 2017) for overview; Rice and Pan, 2021). Also, it would be worthwhile repeating this same study by exploring a range of different leisure activities, recognizing that park visitation is influenced by leisure motivation (Kabisch et al, 2021).…”
Section: Implications For Ugi Managementmentioning
confidence: 99%
“…Nature contact estimates from "big data" datasets (e.g., Google mobility, Strava, Geotagged Instagram images) did not provide precise definitions of 'natural environments', may have counted multiple visits by the same individuals and might not be representative of the larger population due to inability to obtain data from individuals who are not either using the apps or sharing their location information. All the big data studies identified in this review revealed considerable increases in nature contact (Lu et al, 2021b;Rice and Pan, 2021;Venter et al, 2020), whereas smaller datasets (e.g., survey data) utilized by studies in this review reported mixed findings regarding nature contact during the lockdown (Grima et al, 2020;Heo et al, 2021;Ugolini et al, 2021). Rice and Pan (2021) emphasized the need to validate big data inferred changes in nature visitation.…”
Section: Opportunities For Nature Exposurementioning
confidence: 87%
“…All the big data studies identified in this review revealed considerable increases in nature contact (Lu et al, 2021b;Rice and Pan, 2021;Venter et al, 2020), whereas smaller datasets (e.g., survey data) utilized by studies in this review reported mixed findings regarding nature contact during the lockdown (Grima et al, 2020;Heo et al, 2021;Ugolini et al, 2021). Rice and Pan (2021) emphasized the need to validate big data inferred changes in nature visitation. They further argued that changes in visits to the natural environment might be influenced by the difficulty and comfort with being outside as a result of the topographic setting of the study site and its seasonal climate conditions rather than the COVID lockdown alone.…”
Section: Opportunities For Nature Exposurementioning
confidence: 87%
See 1 more Smart Citation
“…As a result, obtaining up-to-date information about how people use and visit natural areas by traditional means may be laborious, time-consuming, and costly [15]. Further, some aspects of park visitation are inherently spatial and thus require analyses that incorporate spatial components [16], something that traditional methods may fail to do in a timely or effective manner, especially during a pandemic.…”
Section: Introductionmentioning
confidence: 99%